F3-INTERIOR E-COMMERCE APPLICATION USING 3D VIEW WEBGL REACT THREE FIBER BASED ON ANDROID - Wicaksono, Danang Wahyu; Samsudin (Politeknik Ganesha Medan, 2023)
The development of technology in this era is growing rapidly and has a big effect on the wearer, especially in the world of business. Buying and selling interior furniture manufacturing services is still fairly manual. With the development of information technology, the introduction of interior and exterior furniture can be done using a smartphone or personal computer. People sometimes still experience problems in choosing the right furniture and texture choices. The previous online buying and selling system also lacked the desired texture or color selection, so that orders were still fairly rigid and did not match the wishes of consumers. Based on these problems, this research created an application that can assist consumers in exploring the desired furniture, from setting the color and texture atmosphere. By using WebGl (Web Graphic Library) which makes it easier for consumers to see an overview of interior furniture in the form of a 3D (Three Dimensional) view. but WebGl itself can only be displayed via the website, so the author here will use packages that help React Three Fiber which can render WebGl on Android. The results of this study produce the output of an application that displays 3D on furniture items, which can also change the material texture or color in real-time (real).